Sistem Pelacakan Objek Menggunakan Kombinasi Algoritma Optical Flow dan Template Matching - Ahmad Fahriannur; Ronny Mardiyanto; Meilana Siswanto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This study aimed to develop a tracking system algorithm by combining optical flow and template matching algorithms to strengthen tracking and minimize the resulting errors. The system has been tested on a football video game with the ball as a tracking object. The optical flow and template matching algorithms are used interchangeably based on the coordinates of both ranges calculated using the Euclidean distance equation. The result shows that the system is able to do tracking, although it is temporarily blocked by other objects, more stable and the distance error between the coordinates of the tracking result and the actual coordinates is not more than 110 pixels compared to using only optical flow or template matching algorithm.